Efficient layer stopping technique for layered LDPC decoding. Issue 16 (1st August 2013) - Lin, C.‐H.; Huang, T.‐H.; Chen, C.‐C.; Lin, S.‐Y.
Abstract : Early termination techniques are widely used in low‐density party‐check (LDPC) decoding since the decoding operations can be tremendously reduced. A layer stopping criterion is proposed to reduce further the operations within iterative layered LDPC decoding. The proposed criterion detects the high reliability of the soft log‐likelihood ratio with a threshold in each layer. Then the layer operations can be stopped when the reliable layers are detected. The proposed criterion combined with early termination techniques can efficiently reduce the layer operations by up to 60% with a negligible loss of coding gain at Eb / N 0 of 3.2 dB.